(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the study of proverbs as an object of axiological linguistics. It is noted that proverbs are of great value for axiological linguistics, allowing the study of both linguistic semantics and cultural phenomena. Proverbs represent valuable material for the study of the axiosphere of language and culture, since they, as an object of axiological linguistics, reflect the value system and worldview of the native speaker and demonstrate an attitude towards significant cultural concepts, such as age, wealth, health. Analysis of the proverbial fund allows us to reveal the basic values and anti-values that underlie the mentality of the people.